(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In several areas in science and engineering is widely using the principle in dispersion and absorption of electromagnetic waves. The remote sensing strategies for the analysis and monitoring of the consistency of materials involve multiple artifacts. They are used widely in fields such as radio physics, radiology, biophysics and optics in materials, colloids, and the properties in radio wave propagations and various artifacts, atmospheric and ocean optics, climatology and ecology.